2019
DOI: 10.1111/1742-6723.13358
|View full text |Cite
|
Sign up to set email alerts
|

Introducing routine risk assessment for occupational violence and aggression in the emergency department

Abstract: In reference to the recent work on understanding economic evaluation alongside emergency medicine research by Singh et al 1 , we would like to draw attention to the selection of the discount rate when performing an economic analysis. This choice has implications in that a figure in the lower ranges may overestimate the value of an outcome or the cost of an intervention or project. A higher rate may result in less promising results and may even be enough to send a potential capital investment's Net Present Valu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 3 publications
0
15
0
Order By: Relevance
“…This finding of perpetrator diversity casts doubt in the presumed success of a one‐size fits all solution, such as de‐escalation training or a zero‐tolerance policy. Despite this, organisational interest in structured risk assessment tools continues 18 …”
Section: Discussionmentioning
confidence: 99%
“…This finding of perpetrator diversity casts doubt in the presumed success of a one‐size fits all solution, such as de‐escalation training or a zero‐tolerance policy. Despite this, organisational interest in structured risk assessment tools continues 18 …”
Section: Discussionmentioning
confidence: 99%
“…Reports can be as low as Ryan and Maguire's (2006) report of 3% in an Irish ED up to an estimated 91.5% in Italy (Ramacciati et al, 2019) (see Table 1). A recent review confirmed that this disparity and difference in percentages is common across the literature (Nikathil et al, 2017), although it must be noted that some of the studies where higher rates were observed included to small local samples (Ogundipe et al, 2013;Wright-Brown et al, 2016).…”
Section: Extent Of Violence In the Emergency Departmentmentioning
confidence: 93%
“…Defining the exact nature and prevalence of violence has always been problematic. As early as 2002, Krug et al reported the difficulty in getting an accurate measure of the scale of the phenomenon due to incident reporting not always being completed, even in health services that supported reporting (Ryan & Maguire, 2006).…”
Section: Extent Of Violence In the Emergency Departmentmentioning
confidence: 99%
See 2 more Smart Citations